(untitled) (Research, Society and Development, 2020)
Some accidents caused by mining are related to the disposal of waste from the mining process. There is currently a great debate about the best method of decommissioning existing dams and storing the new tailings. Based on the cost analysis, this project was developed with the objective of measuring the fall in the NPV value of an iron mining enterprise that chose to use the material existing in the dam together with the material extracted from the mine in its beneficiation process. Using the NPV Scheduler software, which uses the Lerchs and Grossmann algorithm as operating principle, some scenarios were produced in Single and Multi-Mine modes, which were compared. Considering an ideal scenario from an economic point of view to determine the drop in profits caused by decommissioning. After problems during the setting up of scenarios such as the incorrect generation of pushbacks and the massing of masses, solved using some manual calculations and application of techniques known as Pre-Stripping, it was possible to define the economic impact generated by the resumption of the dam.